Grip strength among Indigenous and non-Indigenous Australian adults: a longitudinal study of the effects of birth size and current size. Issue 4 (2nd April 2019) - Howarth, Timothy; Davison, Belinda; Singh, Gurmeet
Abstract : Objectives: Indigenous Australians are born smaller than non-Indigenous Australians and are at an increased risk of early onset of frailty. This study aimed to identify the relationship between birth size, current size and grip strength, as an early marker of frailty, in Indigenous and non-Indigenous young adults. Design: Cross sectional data from two longitudinal studies: Aboriginal birth cohort (Indigenous) and top end cohort (non-Indigenous). Setting: Participants reside in over 40 urban and remote communities across the Northern Territory, Australia. Participants: Young adults with median age 25 years (IQR 24–26); 427 participants (55% women), 267 (63%) were remote Indigenous, 55 (13%) urban Indigenous and 105 (25%) urban non-Indigenous. Outcome measures: Reliable birth data were available. Anthropometric data (height, weight, lean mass) and grip strength were directly collected using standardised methods. Current residence was classified as urban or remote. Results: The rate of low birthweight (LBW) in the non-Indigenous cohort (9%) was significantly lower than the Indigenous cohort (16%) (−7%, 95% CI −14 to 0, p=0.03). Indigenous participants had lower grip strength than non-Indigenous (women, −2.08, 95% CI −3.61 to –0.55, p=0.008 and men, −6.2, 95% CI −9.84 to –2.46, p=0.001). Birth weight (BW) was associated with grip strength after adjusting for demographic factors for both women (β=1.29, 95% CI 0.41 to 2.16, p=0.004) and men (β=3.95, 95% CI 2.38 to 5.51, p<0.001). When current size (lean mass and body mass index [BMI]) was introduced to the model BW was no longer a significant factor. Lean mass was a positive indicator for grip strength, and BMI a negative indicator. Conclusions: As expected women had significantly lower grip strength than men. Current size, in particular lean mass, was the strongest predictor of adult grip strength in this cohort. BW may have an indirect effect on later grip strength via moderation of lean mass development, especially through adolescence and young adulthood.